Purchase intention of Gen Z university students over the tiktok shop facilitated by hyper-personalization - Koh, Yi Xiang; Lim, Jun Hao (2025)
This study focuses on investigating the purchase intentions of Generation Z university students in Malaysia towards TikTok Shops, with a focus on the role of hyper-personalization in the Technology Acceptance Model (TAM2). Six variables were investigated, which included social media experience, mobile device specs, internet connectivity, perceived ease of use, perceived usefulness, and hyperpersonalization. Data were gathered using a structured questionnaire posted online, with 210 valid responses analyzed using PLS-SEM. The data show that social media experience and internet connectivity have significant effects on perceived usefulness, but mobile device specifications will not significantly affect. Furthermore, perceived usefulness has a significant effect on purchase intention, whereas perceived ease of use does not. However, when mediated by hyper-personalization, perceived ease of use becomes significant, indicating the importance of hyper-personalization in increasing user engagement and buying behavior. The study adds on TAM2 by incorporating hyper-personalization as a mediating variable, providing theoretical insights into the acceptance of social media e-commerce. In practice, the findings suggest that firms should emphasize increasing internet reliability, develop hyper-personalization tools, and assure user-friendly regulations to increase purchase intentions among Gen Z consumers. This study contributes to the understanding of technology adoption in social media e-commerce and provides practical advice for marketers looking to maximize TikTok Shop's potential. Keywords: TAM 2, Gen Z, Hyper-personalization, Social Media e-commerce, Purchase Intention Subject Area: HF5410-5417.5 Marketing. Distribution of products